Video conferencia Zoom y su incidencia en el proceso de aprendizaje en la asignatura de Lengua y Literatura del séptimo grado paralelo “A” sección matutina de la Escuela de Educación Básica “Miguel Riofrío” de la ciudad de Loja periodo académico 2020 – 2021. Lineamientos alternativos - Mendoza Jiménez, Rita Maribel (2021)
The present research work has as general objective: To determine how the Zoom videoconference affects the learning process of the students of the seventh grade parallel "A" morning section of the School of Basic Education "Miguel Riofrío" of the city of Loja, academic period 2020 - 2021, considering that due to a pandemic, education suffered a forced adjustment to the virtual modality. The applied research is of a non-experimental quantitative type, assuming that the independent variable "Zoom Videoconference" is already existing. The methods used were scientific, observational and statistical. The instruments that made it possible to identify the information necessary for the analysis were: observation guide and questionnaire, applied through an online survey using Google Forms as a resource. The information collected was analyzed using the statistical method and allowed to discover the advantages and disadvantages of using Zoom in the learning process of students, in addition, it was determined that the main resource to teach classes in times of pandemic is the Zoom videoconference, which means that this application plays an important role in the transmission of knowledge and contributesto the development of theirintellectual capacities. It is proposed as an alternative guideline to guarantee the correct use of the Zoom videoconference, an explanatory guide of the important functions in the development of the class, prioritizing dynamism and interaction as a fundamental component of the integral formation of the student.